Analisis Input-Output: Peranan Industri Terkait Pariwisata di Provinsi Sumatera Barat - Lili Triana Wardatul Jannah; Etjih Tasriah (Jurnal Ekonomi Pembangunan, 2022)
In the 2016-2021 RPJMD, West Sumatra’s government made tourism as one of its development priorities. The rapid development of tourism-related industries in West Sumatra is not in line with the declining economic growth every year. Then, in 2020, the COVID-19 pandemic caused a slump in various industries, especially those related to tourism. Therefore, researchers will identify the role of the tourism-related industry on the economy in West Sumatra and the impact of the decline in tourism-related industry performance due to the COVID-19 pandemic on the West Sumatra economy. This study uses input-output table analysis including linkage analysis, multiplier analysis, and impact simulation analysis. Based on the research results, the land transportation industry, air transportation, company services, and other services are the leading industries in tourism-related industries. Then, the tourism-related industry in West Sumatra is pro-growth and pro-poor which means the tourism-related industry has the ability to increase economic growth and the welfare of the people in West Sumatra. Through impact simulations, the decline in tourism-related industry performance due to the COVID-19 pandemic has resulted in a decrease in total output, a decrease in household income, and a decrease in job opportunities in West Sumatra.